Semiotic Analysis of Masculine Representation in “Padman”: Exploring Denotation, Connotation, and Myth - Wahyuni, Sri; setyowati, Yulis; A.Y.P.S, Shanty Duwila (TELL - US JOURNAL, 2024)
This study employs a qualitative research design to examine the representation of masculinity in the film "Padman" through a semiotic analysis. Utilizing Barthes' semiotic framework, the research explores how denotative, connotative, and mythic elements construct the character of Lakshminkant, played by Akshay Kumar. The analysis reveals that Lakshminkant embodies a form of masculinity that diverges from traditional portrayals, emphasizing empathy, resilience, and innovation over physical strength and aggression. Visual cues such as his traditional attire and confident yet humble body language, alongside his engagement in physical labor, highlight his connection to rural roots and industrious nature. His focus on menstrual hygiene, a taboo subject in many parts of India, challenges patriarchal norms and promotes gender equality. The study finds that Lakshminkant's character redefines heroism by aligning it with perseverance, moral courage, and social innovation. This redefinition challenges hegemonic masculinity and offers a progressive model of manhood that values emotional and social intelligence. Additionally, the film's portrayal of Lakshminkant as a benevolent innovator underscores the potential of individuals to drive social change, suggesting that modernity can coexist with traditional values. Theoretical application of Barthes' semiotic framework proved effective in uncovering the layers of meaning within the film, providing a comprehensive understanding of its portrayal of masculinity. This research contributes to the discourse on gender roles in Indian cinema and highlights the importance of inclusive representations in promoting societal change.